2021
DOI: 10.21203/rs.3.rs-453378/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-Temporal Changes of Snow Cover and Its Relationship With Meteorological Factors on the Qinghai-Tibet Plateau, China

Abstract: The Qinghai-Tibet Plateau (TP) is one of the most sensitive areas to climate change, and its ecological environment changes directly or indirectly reflect the global climate change trend. The snow cover ratio (SCR) is an important indicator reflecting the climate and environmental changes of the TP. The daily remote sensing data of snow cover on the TP from 2003 to 2014 were used to study the spatio-temporal distribution of snow cover on the TP. The results have shown that the average snowmelt day on the TP st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…NPP serves as a vital parameter for assessing changes in terrestrial ecosystems and evaluating their sustainability [2][3][4]. It is one of the key indicators of the material foundation for ecosystem development [5,6] and plays a significant role in ecosystem assessment processes [7][8][9][10]. Furthermore, it is influenced by climate change [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…NPP serves as a vital parameter for assessing changes in terrestrial ecosystems and evaluating their sustainability [2][3][4]. It is one of the key indicators of the material foundation for ecosystem development [5,6] and plays a significant role in ecosystem assessment processes [7][8][9][10]. Furthermore, it is influenced by climate change [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In summer, the common weather systems over the QTP include the plateau shear line, vortex, and low trough [7][8][9]. Large-scale circulation combined with intense surface heating and active near-surface turbulence makes the convection activity very active over the QTP [4,10,11]. According to the "Atlas of China Disastrous Weather and Climate" issued by the Chinese Meteorological Administration [12], the central QTP presents approximately 80 thunderstorm days per year, and the number of thunderstorm days throughout the central and eastern QTP is apparently greater than those over Central and Eastern China at the same latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies directly focusing on the thunderstorm activity throughout the QTP are rare, but the existing studies based on the thunderstorm cases or concerned with the convection systems over the QTP have indicated that the characteristics of the thunderstorms over the QTP may be unique. For example, convective clouds over the QTP can constitute up to 90% of the total clouds in the central QTP [10,18], and the strong convective clouds over the QTP account for approximately 4-21% of cloud types, approximating five times that of other places in China [19]. Convective clouds over the QTP are typically isolated and have densely packed cloud tops, showing "popcorn-like" or "tower-mast-like" shapes [4,20,21].…”
Section: Introductionmentioning
confidence: 99%